Solitary bronchial squamous cell papilloma – another human papillomavirus (HPV)-associated benign tumor: systematic review and meta-analysis - Syrjänen, Kari; Syrjänen, Stina (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To perform a systematic review and formal meta-analysis of the literature reporting on HPV detection in bronchial squamous cell papillomas (SCP). Material and methods : The literature was searched up to June 2012. The effect size was calculated as event rate (95% CI), with homogeneity testing using Cochran’s Q and I2 statistics. Meta-regression was used to test the impact of study-level covariates (HPV detection method, geographic origin) on effect size, and potential publication bias was estimated using funnel plot symmetry. Results : Fifteen studies were eligible, covering 89 bronchial SCPs from different geographic regions. Altogether, 38 (42.7%) cases tested HPV-positive; effect size 0.422 (95% CI: 0.311–0.542; fixed effects model), and 0.495 (95% CI: 0.316–0.675; random effects model). In meta-analysis stratified by i) HPV detection technique and ii) geographic study origin, the between-study heterogeneity was not significant for either; p = 0.348, and p = 0.792, respectively. In maximum likelihood meta-regression, HPV detection method (p = 0.150) and geographic origin of the study (p = 0.164) were not significant study-level covariates. Some evidence for publication bias was found only among in situ hybridization (ISH)-based studies and among studies from Europe, but with a negligible effect on summary effect size estimates. In sensitivity analysis, the meta-analytic results were robust to all one-by-one study removals. Conclusions : In formal meta-regression, the variability in HPV detection rates reported in bronchial SCPs is not explained by the HPV detection method or geographic origin of the study.